Ultrastructural characteristics of oligodendrocyte precursor cells in the early postnatal mouse optic nerve observed by serial block-face scanning electron microscopy - Katsuhiko Ono; Hitoshi Gotoh; Tadashi Nomura; Tsuyoshi Morita; Otto Baba; Mami Matsumoto; Sei Saitoh; Nobuhiko Ohno (PLoS ONE, 2022)
Oligodendrocyte precursor cells (OPC) arise from restricted regions of the central nervous system (CNS) and differentiate into myelin-forming cells after migration, but their ultrastructural characteristics have not been fully elucidated. This study examined the three-dimensional ultrastructure of OPCs in comparison with other glial cells in the early postnatal optic nerve by serial block-face scanning electron microscopy. We examined 70 putative OPCs (pOPC) that were distinct from other glial cells according to established morphological criteria. The pOPCs were unipolar in shape with relatively few processes, and their Golgi apparatus were localized in the perinuclear region with a single cisterna. Astrocytes abundant in the optic nerve were distinct from pOPCs and had a greater number of processes and more complicated Golgi apparatus morphology. All pOPCs and astrocytes contained a pair of centrioles (basal bodies). Among them, 45% of pOPCs extended a short cilium, and 20% of pOPCs had centrioles accompanied by vesicles, whereas all astrocytes with basal bodies had cilia with invaginated ciliary pockets. These results suggest that the fine structures of pOPCs during the developing and immature stages may account for their distinct behavior. Additionally, the vesicular transport of the centrioles, along with a short cilium length, suggests active ciliogenesis in pOPCs.